Description of new species Macellicephaloides veronikae sp. n. (Polynoidae, Annelida) from the Amundsen Sea, Southern Ocean - Lenka Neal; Helena Wiklund; Adrian G. Glover (Polar Biology, 2025)
While the Southern Ocean represents a unique habitat, currently undergoing rapid environmental change, its biodiversity remains largely unknown, particularly at greater depths. Increased sampling efforts in the Amundsen Sea, a previously unexplored region of the Southern Ocean, combined with the use of an epibenthic sledge resulted in a large collection of mobile, scale-bearing worms from the family Polynoidae Kinberg, 1856. The greatest taxonomic novelty in the material collected from the Pine Island Bay, Amundsen Sea, was found within the exclusively deep-sea subfamily Macellicephalinae Hartmann-Schröder, 1971. Examination of this material has already led to formalization of six new species of Macellicephala (Neal et al. 2018). This study represents the continuation of such effort with formalization of Macellicephaloides veronikae sp. n. based on morphology and 16S and 18S molecular markers. In the phylogenetic analyses, the new species is sister taxon to Macellicephaloides moustachu from the abyssal equatorial Pacific Ocean, albeit based on very limited taxon sampling currently available. Macellicephaloides veronikae sp. n. shows the shallowest distribution (500–1000 m) of this genus recorded to date and may represent a case of polar emergence.

On Anguillosyllis cf. hessleri Maciolek, 2020 – A species complex from the Clarion-Clipperton zone, abyssal central Pacific - Regan Drennan; Lenka Neal; Helena Wiklund; Eva C.D. Stewart; Muriel Rabone; Corie Boolukos; Innes Clatworthy; Zuzana Jungmanova; Thomas G. Dahlgren; Adrian G. Glover (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

A new species of Erinaceusyllis (Annelida: Syllidae) discovered at a wood-fall in the eastern Clarion-Clipperton zone, central Pacific ocean - Christian L. Nilsson; Helena Wiklund; Adrian G. Glover; Guadalupe Bribiesca-Contreras; Thomas G. Dahlgren (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Diversity and phylogeny of demosponge fauna in the abyssal nodule fields of the eastern Clarion‐Clipperton Zone, Pacific Ocean - Swee‐Cheng Lim; Helena Wiklund; Guadalupe Bribiesca‐Contreras; Adrian G. Glover; Thomas G. Dahlgren; Koh‐Siang Tan (Zoologica Scripta, 2024)
More than 7000 demosponge species have been described to date globally but Plenaster craigi , the most common and abundant species in the eastern CCZ, represents a new family, and possibly in a new order. Interestingly, P. craigi and members of the families Polymastiidae and Hamacanthidae, all filter‐feeding demosponge species, are far more abundant in nodule fields than the carnivorous sponges (Cladorhizidae) which were widely known to be the most dominant demosponge group in the abyssal depths. Lastly, it is highly likely that such tiny demosponges are present in other habitats. They might have been overlooked and/or ignored by sponge researchers in the past due to their tiny size and nondescript habitus. These demosponges could be distinct new species, not juveniles or indeterminates and warrant full taxonomic treatment.

Abyssal fauna of polymetallic nodule exploration areas, eastern Clarion-Clipperton Zone, central Pacific Ocean: Annelida: Spionidae and Poecilochaetidae - Lenka Neal; Helena Wiklund; Muriel Rabone; Thomas G. Dahlgren; Adrian G. Glover (Marine Biodiversity, 2022)
This paper represents a continuation of taxonomic publications on the benthic fauna of polymetallic nodule fields in the eastern Clarion-Clipperton Zone (CCZ) using material collected during baseline environmental survey work targeting two exploration contract areas (“UK-1” and “OMS”) and one Area of Particular Environmental Interest, “APEI-6.” Families Poecilochaetidae Hannerz, 1956 and Spionidae Grube, 1850 of the annelid suborder Spioniformia were studied here. Taxonomic data are presented for 25 species from 98 records as identified by a combination of morphological and genetic approaches. Although sub-optimal morphological condition can prevent new species being formally described, it is essential that morphological, molecular, and voucher data are made available for future surveys. Descriptions of two new species— Poecilochaetus brenkei sp. nov. and Laonice shulseae sp. nov.—increase the number of formally described new annelid species from the areas targeted in this study to 15 and CCZ-wide to 46. We also discuss the commonly reported “cosmopolitan” deep-sea spionid Aurospio dibranchiata Maciolek, 1981, which we show represents several genetically distinct species (three of these from CCZ area alone) but without reliable morphological characters to separate them. Molecular data provide evidence that 15 out of 25 species reported here have a wide distribution within the eastern CCZ and that Aurospio sp. “NHM_2186” and the known species Prionospio amarsupiata Neal & Altamira in Paterson et al. 2016 may be cosmopolitan. Lastly, the molecular data provide insights into relationships within Spioniformia, suggesting that both Poecilochaetidae and Trochochaetidae belong within Spionidae.

Biogeography and Connectivity Across Habitat Types and Geographical Scales in Pacific Abyssal Scavenging Amphipods - Guadalupe Bribiesca-Contreras; Thomas G. Dahlgren; Tammy Horton; Jeffrey C. Drazen; Regan Drennan; Daniel O.B. Jones; Astrid B. Leitner; Kirsty A. McQuaid; Craig R. Smith; Sergio Taboada; Helena Wiklund; Adrian G. Glover (Frontiers in Marine Science, 2021)
Recently, there has been a resurgent interest in the exploration of deep-sea mineral deposits, particularly polymetallic nodules in the Clarion-Clipperton Zone (CCZ), central Pacific. Accurate environmental impact assessment is critical to the effective management of a new industry and depends on a sound understanding of species taxonomy, biogeography, and connectivity across a range of scales. Connectivity is a particularly important parameter in determining ecosystem resilience, as it helps to define the ability of a system to recover post-impact. Scavenging amphipods in the superfamilies Alicelloidea Lowry and De Broyer, 2008 and Lysianassoidea Dana, 1849 contribute to a unique and abundant scavenging community in abyssal ecosystems. They are relatively easy to sample and in recent years have become the target of several molecular and taxonomic studies, but are poorly studied in the CCZ. Here, a molecular approach is used to identify and delimit species, and to investigate evolutionary relationships of scavenging amphipods from both abyssal plain and deep (>3000 m) seamount habitats in three APEIs (Areas of Particular Environmental Interest, i.e., designated conservation areas) in the western CCZ. A total of 17 different morphospecies of scavenging amphipods were identified, which include at least 30 genetic species delimited by a fragment of the cytochrome c oxidase subunit I (COI) barcode gene. The scavenging communities sampled in the western CCZ included the most common species ( Abyssorchomene gerulicorbis (Shulenberger and Barnard, 1976), A. chevreuxi (Stebbing, 1906), Paralicella caperesca Shulenberger and Barnard, 1976, and P. tenuipes Chevreux, 1908) reported for other ocean basins. Only four morphospecies, representing five genetic species, were shared between APEIs 1, 4, and 7. The two abyssal plain sites at APEIs 4 and 7 were dominated by two and three of the most common scavenging species, respectively, while the APEI 1 seamount site was dominated by two species potentially new to science that appeared to be endemic to the site. The presence of common species in all sites and high genetic diversity, yet little geographic structuring, indicate connectivity over evolutionary time scales between the areas, which span about 1500 km. Similar to recent studies, the differences in amphipod assemblages found between the seamount and abyssal sites suggest that ecological conditions on seamounts generate distinct community compositions.

Chiridota heheva—the cosmopolitan holothurian - Elin A. Thomas; Ruoyu Liu; Diva Amon; Jon T. Copley; Adrian G. Glover; Sarah J. Helyar; Karine Olu; Helena Wiklund; Haibin Zhang; Julia D. Sigwart (Marine Biodiversity, 2020)
Chemosynthetic ecosystems have long been acknowledged as key areas of enrichment for deep-sea life, supporting hundreds of endemic species. Echinoderms are among the most common taxa inhabiting the periphery of chemosynthetic environments, and of these, chiridotid holothurians are often the most frequently observed. Yet, published records of chiridotids in these habitats are often noted only as supplemental information to larger ecological studies and several remain taxonomically unverified. This study therefore aimed to collate and review all known records attributed to Chiridota Eschscholtz, 1829, and to conduct the first phylogenetic analysis into the relationship of these chiridotid holothurians across global chemosynthetic habitats. We show that Chiridota heheva Pawson & Vance, 2004 is a globally widespread, cosmopolitan holothurian that occupies all three types of deep-sea chemosynthetic ecosystem—hydrothermal vents, cold seeps and organic falls—as an organic-enrichment opportunist. Furthermore, we hypothesise that C. heheva may be synonymous with another vent-endemic chiridotid, Chiridota hydrothermica Smirnov et al., 2000, owing to the strong morphological, ecological and biogeographical parallels between the two species, and predict that any chiridotid holothurians subsequently discovered at global reducing environments will belong to this novel species complex. This study highlights the importance of understudied, peripheral taxa, such as holothurians, to provide insights to biogeography, connectivity and speciation at insular deep-sea habitats.

High diversity and pan-oceanic distribution of deep-sea polychaetes: Prionospio and Aurospio (Annelida: Spionidae) in the Atlantic and Pacific Ocean - Theresa Guggolz; Karin Meißner; Martin Schwentner; Thomas G. Dahlgren; Helena Wiklund; Paulo Bonifácio; Angelika Brandt (Organisms Diversity & Evolution, 2020)
Prionospio Malmgren 1867 and Aurospio Maciolek 1981 (Annelida: Spionidae) are polychaete genera commonly found in the deep sea. Both genera belong to the Prionospio complex, whose members are known to have limited distinguishing characters. Morphological identification of specimens from the deep sea is challenging, as fragmentation and other damages are common during sampling. These issues impede investigations into the distribution patterns of these genera in the deep sea. In this study, we employ two molecular markers (16S rRNA and 18S) to study the diversity and the distribution patterns of Prionospio and Aurospio from the tropical North Atlantic, the Puerto Rico Trench and the central Pacific. Based on different molecular analyses (Automated Barcode Gap Discovery, GMYC, pairwise genetic distances, phylogenetics, haplotype networks), we were able to identify and differentiate 21 lineages (three lineages composed solely of GenBank entries) that represent putative species. Seven of these lineages exhibited pan-oceanic distributions (occurring in the Atlantic as well as the Pacific) in some cases even sharing identical 16S rRNA haplotypes in both oceans. Even the lineages found to be restricted to one of the oceans were distributed over large regional scales as for example across the Mid-Atlantic Ridge from the Caribbean to the eastern Atlantic (> 3389 km). Our results suggest that members of Prionospio and Aurospio may have the potential to disperse across large geographic distances, largely unaffected by topographic barriers and possibly even between oceans. Their high dispersal capacities are probably explained by their free-swimming long-lived planktonic larvae.

Taxonomy and phylogeny of mud owls (Annelida: Sternaspidae), including a new synonymy and new records from the Southern Ocean, North East Atlantic Ocean and Pacific Ocean: challenges in morphological delimitation - Regan Drennan; Helena Wiklund; Greg W. Rouse; Magdalena N. Georgieva; Xuwen Wu; Genki Kobayashi; Kenji Yoshino; Adrian G. Glover (Marine Biodiversity, 2019)

Implications of population connectivity studies for the design of marine protected areas in the deep sea: An example of a demosponge from the Clarion‐Clipperton Zone - Sergi Taboada; Ana Riesgo; Helena Wiklund; Gordon L. J. Paterson; Vasiliki Koutsouveli; Nadiezhda Santodomingo; Andrew C. Dale; Craig R. Smith; Daniel O. B. Jones; Thomas G. Dahlgren; Adrian G. Glover (Molecular Ecology, 2018)
The abyssal demosponge Plenaster craigi inhabits the Clarion‐Clipperton Zone ( CCZ ) in the northeast Pacific, a region with abundant seafloor polymetallic nodules with potential mining interest. Since P. craigi is a very abundant encrusting sponge on nodules, understanding its genetic diversity and connectivity could provide important insights into extinction risks and design of marine protected areas. Our main aim was to assess the effectiveness of the Area of Particular Environmental Interest 6 ( APEI ‐6) as a potential genetic reservoir for three adjacent mining exploration contract areas ( UK ‐1A, UK ‐1B and OMS ‐1A). As in many other sponges, COI showed extremely low variability even for samples ~900 km apart. Conversely, the 168 individuals of P. craigi, genotyped for 11 microsatellite markers, provided strong genetic structure at large geographical scales not explained by isolation by distance (IBD). Interestingly, we detected molecular affinities between samples from APEI ‐6 and UK ‐1A, despite being separated ~800 km. Although our migration analysis inferred very little progeny dispersal of individuals between areas, the major differentiation of OMS ‐1A from the other areas might be explained by the occurrence of predominantly northeasterly transport predicted by the HYCOM hydrodynamic model. Our study suggests that although APEI ‐6 does serve a conservation role, with species connectivity to the exploration areas, it is on its own inadequate as a propagule source for P. craigi for the entire eastern portion of the CCZ . Our new data suggest that an APEI located to the east and/or the south of the UK ‐1, OMS ‐1, BGR , TOML and NORI areas would be highly valuable.

Mitochondrial genome and polymorphic microsatellite markers from the abyssal sponge Plenaster craigi Lim & Wiklund, 2017: tools for understanding the impact of deep-sea mining - Sergi Taboada; Nathan J. Kenny; Ana Riesgo; Helena Wiklund; Gordon L. J. Paterson; Thomas G. Dahlgren; Adrian G. Glover (Marine Biodiversity, 2018)

Distributional Patterns of Polychaetes Across the West Antarctic Based on DNA Barcoding and Particle Tracking Analyses - Madeleine J. Brasier; James Harle; Helena Wiklund; Rachel M. Jeffreys; Katrin Linse; Henry A. Ruhl; Adrian G. Glover (Frontiers in Marine Science, 2017)

A new genus and species of abyssal sponge commonly encrusting polymetallic nodules in the Clarion-Clipperton Zone, East Pacific Ocean - Swee-Cheng Lim; Helena Wiklund; Adrian G. Glover; Thomas G. Dahlgren; Koh-Siang Tan (Systematics and Biodiversity, 2017)

Is the Antarctic Ophryotrocha orensanzi (Annelida: Dorvilleidae) a circumpolar non-specialized opportunist? - Hannelore Paxton; Helena Wiklund; Frances Alexander; Sergi Taboada (Systematics and Biodiversity, 2017)

An End-to-End DNA Taxonomy Methodology for Benthic Biodiversity Survey in the Clarion-Clipperton Zone, Central Pacific Abyss - Adrian Glover; Thomas Dahlgren; Helena Wiklund; Inga Mohrbeck; Craig Smith (Journal of Marine Science and Engineering, 2015)
Recent years have seen increased survey and sampling expeditions to the Clarion-Clipperton Zone (CCZ), central Pacific Ocean abyss, driven by commercial interests from contractors in the potential extraction of polymetallic nodules in the region. Part of the International Seabed Authority (ISA) regulatory requirements are that these contractors undertake environmental research expeditions to their CCZ exploration claims following guidelines approved by the ISA Legal and Technical Commission (ISA, 2010). Section 9 (e) of these guidelines instructs contractors to “…collect data on the sea floor communities specifically relating to megafauna, macrofauna, meiofauna, microfauna, nodule fauna and demersal scavengers”. There are a number of methodological challenges to this, including the water depth (4000–5000 m), extremely warm surface waters (~28 °C) compared to bottom water (~1.5 °C) and great distances to ports requiring a large and long seagoing expedition with only a limited number of scientists. Both scientists and regulators have recently realized that a major gap in our knowledge of the region is the fundamental taxonomy of the animals that live there; this is essential to inform our knowledge of the biogeography, natural history and ultimately our stewardship of the region. Recognising this, the ISA is currently sponsoring a series of taxonomic workshops on the CCZ fauna and to assist in this process we present here a series of methodological pipelines for DNA taxonomy (incorporating both molecular and morphological data) of the macrofauna and megafauna from the CCZ benthic habitat in the recent ABYSSLINE cruise program to the UK-1 exploration claim. A major problem on recent CCZ cruises has been the collection of high-quality samples suitable for both morphology and DNA taxonomy, coupled with a workflow that ensures these data are made available. The DNA sequencing techniques themselves are relatively standard, once good samples have been obtained. The key to quality taxonomic work on macrofaunal animals from the tropical abyss is careful extraction of the animals (in cold, filtered seawater), microscopic observation and preservation of live specimens, from a variety of sampling devices by experienced zoologists at sea. Essential to the long-term iterative building of taxonomic knowledge from the CCZ is an “end-to-end” methodology to the taxonomic science that takes into account careful sampling design, at-sea taxonomic identification and fixation, post-cruise laboratory work with both DNA and morphology and finally a careful sample and data management pipeline that results in specimens and data in accessible open museum collections and online repositories.

First account on the diversity of Ophryotrocha (Annelida, Dorvilleidae) from a mammal-fall in the deep-Atlantic Ocean with the description of three new species - Ascensão Ravara; Ana R. Marçal; Helena Wiklund; Ana Hilário (Systematics and Biodiversity, 2015)

First clues on the ecology of whale falls in the deep A tlantic O cean: results from an experiment using cow carcasses - Ana Hilario; Marina R. Cunha; Luciana Génio; Ana Raquel Marçal; Ascensão Ravara; Clara F. Rodrigues; Helena Wiklund (Marine Ecology, 2015)
Sunken whale carcasses, known as ‘whale falls’, deliver large pulses of organic material to the seafloor and serve as habitat islands for unique assemblages of deep‐sea fauna that include generalist scavenging species, chemosynthetic fauna related to those from hydrothermal vents and cold seeps, and bone‐specialist species. Despite the growing interest in this peculiar habitat in the last decade, all long‐term studies of deep‐sea whale‐falls have been restricted to the Pacific and the ecology of these habitats in the Atlantic Ocean has been overlooked. Here we report the first study on large mammal carcasses in the deep Atlantic Ocean. Cow carcasses amounting to 570 kg were deployed at 1000 m in the Setubal canyon, where cetaceans naturally occur. Eighteen months after deployment, all soft tissues had been consumed and the visible remains of the carcasses consisted solely of skeletal material that supported a diverse macrofaunal assemblage distinct from that of the background, including organic‐enrichment respondents, sulphophiles and bone‐specialists. The trophic structure of this assemblage denotes an overlap of successional stages previously described in whale falls. Our results provide important insights into the contribution of mammal falls to deep‐sea biodiversity in the NE Atlantic, species distribution and biogeography of bone specialists, and the potential role of these habitats as dispersal stepping‐stones for vent and seep species. Additionally we show that cow carcasses may serve as an accessible model system for the study of ecological processes at deep‐sea whale‐falls.

Different mating expenditure in response to sperm competition risk between generations in the bivoltine butterfly Pieris napi - Helena Larsdotter-Mellström; Christer Wiklund (Behavioral Ecology and Sociobiology, 2015)

Molecular taxonomy of Osedax (Annelida: Siboglinidae) in the Southern Ocean - Diva J. Amon; Helena Wiklund; Thomas G. Dahlgren; Jonathan T. Copley; Craig R. Smith; Alan J. Jamieson; Adrian G. Glover (Zoologica Scripta, 2014)
We report the discovery of three new species of Osedax in the deep Southern Ocean, expanding the diversity and geographical range of this genus of bone‐eating worms. Osedax rogersi sp. n. and Osedax crouchi sp. n. were found on a whale skeleton at 1444 m in the Kemp Caldera in the East Scotia Sea during the Chemosynthetic Ecosystems of the Southern Ocean (ChEsSo) project. The recently described species, Osedax antarcticus , found on whale bones implanted at a depth of 550–650 m off Smith Island in the Bransfield Strait, was also found inhabiting the whale skeleton in the Kemp Caldera. Osedax crouchi as well as another new species Osedax nordenskjoeldi sp. n. have also been found on the implanted whale bones off Smith Island. These two localities are approximately 1800 km apart demonstrating a wide distribution of species within the genus. We describe the three new species, O. rogersi, O. crouchi and O . nordenskjoeldi and report the second record of O. antarcticus . We also present a new phylogenetic analysis for Osedax , including data examining genetic connectivity between the Scotia Arc and the Bransfield Strait.

Two new Antarctic Ophryotrocha (Annelida: Dorvilleidae) described from shallow-water whale bones - Sergi Taboada; Helena Wiklund; Adrian G. Glover; Thomas G. Dahlgren; Javier Cristobo; Conxita Avila (Polar Biology, 2013)

Polynoid polychaetes of the Mid-Atlantic Ridge and a new holothurian association - Mark A. Shields; Adrian G. Glover; Helena Wiklund (Marine Biology Research, 2013)

Autonomic nerve system responses for normal and slow rewarmers after hand cold provocation: effects of long-term cold climate training - Helge Brändström; Urban Wiklund; Marcus Karlsson; Karl-Axel Ängquist; Helena Grip; Michael Haney (International Archives of Occupational and Environmental Health, 2013)

Systematics and biodiversity of Ophryotrocha (Annelida, Dorvilleidae) with descriptions of six new species from deep-sea whale-fall and wood-fall habitats in the north-east Pacific - Helena Wiklund; Iris V. Altamira; Adrian G. Glover; Craig R. Smith; Amy R. Baco; Thomas G. Dahlgren (Systematics and Biodiversity, 2012)

Timing of Male Sex Pheromone Biosynthesis in a Butterfly – Different Dynamics under Direct or Diapause Development - Helena Larsdotter-Mellström; Rushana Murtazina; Anna-Karin Borg-Karlson; Christer Wiklund (Journal of Chemical Ecology, 2012)

Seasonal polyphenism in life history traits: time costs of direct development in a butterfly - Helena Larsdotter Mellström; Magne Friberg; Anna-Karin Borg-Karlson; Rushana Murtazina; Mikael Palm; Christer Wiklund (Behavioral Ecology and Sociobiology, 2010)

High symbiont diversity in the bone‐eating worm Osedax mucofloris from shallow whale‐falls in the North Atlantic - Caroline Verna; Alban Ramette; Helena Wiklund; Thomas G. Dahlgren; Adrian G. Glover; Françoise Gaill; Nicole Dubilier (Environmental Microbiology, 2010)
Summary Osedax worms are whale‐fall specialists that infiltrate whale bones with their root tissues. These are filled with endosymbiotic bacteria hypothesized to provide their hosts with nutrition by extracting organic compounds from the whale bones. We investigated the diversity and distribution of symbiotic bacteria in Osedax mucofloris from shallow‐water whale‐falls in the North Atlantic using comparative 16S rRNA sequence analysis and fluorescence in situ hybridization (FISH). We observed a higher diversity of endosymbionts than previously described from other Osedax species. Endosymbiont sequences fell into eight phylogenetically distinct clusters (with 91.4–98.9% similarity between clusters), and considerable microdiversity within clusters (99.5–99.7% similarity) was observed. Statistical tests revealed a highly significant effect of the host individual on endosymbiont diversity and distribution, with 68% of the variability between clusters and 40% of the variability within clusters explained by this effect. FISH analyses showed that most host individuals were dominated by endosymbionts from a single cluster, with endosymbionts from less abundant clusters generally confined to peripheral root tissues. The observed diversity and distribution patterns indicate that the endosymbionts are transmitted horizontally from the environment with repeated infection events occurring as the host root tissues grow into the whale bones.

Phylogenetic relationships within Nephtyidae (Polychaeta, Annelida) - Ascensão Ravara; Helena Wiklund; Marina R. Cunha; Fredrik Pleijel (Zoologica Scripta, 2010)
Ravara, A., Wiklund, H., Cunha, M. R. & Pleijel, F. (2010). Phylogenetic relationships within Nephtyidae (Polychaeta, Annelida). — Zoologica Scripta , 39 , 394–405. We present the first phylogeny of nephtyids, a common, soft‐bottom living polychaete family comprising five genera and over 100 species. Characters used to distinguish nephtyid genera are a matter of controversy and considerable confusion remains as to the generic delineations. The phylogeny is estimated with molecular data from the mitochondrial genes cytochrome oxidase I and 16S rDNA, the nuclear genes 18S rDNA and 28S rDNA and morphological data. The results reveal two well‐supported major clades, corresponding in part to the two main genera of the family, Aglaophamus and Nephtys . The species Nephtys pulchra and Nephtys australiensis are transferred to Aglaophamus , and new diagnoses for the genera are provided. Dentinephtys is synonymized with Nephtys , and Nephtys cornuta is sister to the remaining nephtyids and is referred to the new genus Bipalponephtys , together with Nephtys danida and Micronephthys neotena . Micronephthys is sister to Nephtys and Inermonephtys is of uncertain position.

Biogeography: yesterday, today, and some remarks for the future - Judith Fuchs; Helena Wiklund (Zoologica Scripta, 2010)

Cortical processing of lateral skin stretch stimulation in humans - Helena Backlund Wasling; Linda Lundblad; Line Löken; Johan Wessberg; Katarina Wiklund; Ulf Norrsell; Håkan Olausson (Experimental Brain Research, 2008)

Phylogeny of Hesionidae (Aciculata, Polychaeta), assessed from morphology, 18S rDNA, 28S rDNA, 16S rDNA and COI - Christine Ruta; Arne Nygren; Vincent Rousset; Per Sundberg; Annie Tillier; Helena Wiklund; Fredrik Pleijel (Zoologica Scripta, 2007)
We assess phylogenetic relationships within the polychaete family Hesionidae from morphological data combined with nucleotide data from 18S rDNA, 28S rDNA, 16S rDNA and COI. Parsimony and Bayesian analyses were performed on two data sets; the first was based on a more restricted set of terminals with both morphological and molecular data (17 ingroup terminals), while the second included additional taxa with morphological data only (25 ingroup terminals). The different sets of terminals yielded fully congruent results, as did the parsimony and the Bayesian analyses. Our results indicate high levels of homoplasy in traditionally used morphological characters in the group, and that Hesioninae, Gyptini and Gyptis are nonmonophyletic. Hesionini (mainly Hesione and Leocrates ), Psamathini (mainly Hesiospina , Micropodarke , Nereimyra , Psamathe and Syllidia ), Ophiodrominae (Gyptini and Ophiodromini) and Ophiodromini (mainly Heteropodarke , Ophiodromus and Podarkeopsis ) are monophyletic and agree with previous classifications, and Hesionini is probably the sister to all other hesionids. The placements of the small hesionids capricornia and Lizardia , the hydrothermal vent taxa Hesiodeira and Hesiolyra , and the newly described Hesiobranchia , remain uncertain.